HEARING CORRECTION SYSTEM BASED ON MOBILE COMPUTING PLATFORM - E. S. Azarov; M. I. Vashkevich; S. V. Kozlova; A. A. Petrovsky (Informatika)
An implementation of digital hearing aid based on the mobile computing platform iPhone is proposed. The developed signal processing scheme has a low delay, takes into account characteristics of the computing platform and allows to perform the correction of sensorineural hearing loss. The cor-rection is carried out by linear frequency-dependent amplification and wideband dynamic range com-pression of the signal. In order to take into consideration magnitude characteristic of loudspeakers, the audiometry is performed using iPhone directly. The experimental results of with proposed hearing aid are given.